Effectiveness of The Climacterium Digital Pocket Book on Menopause Readiness - Asmarani, Sri Utami; Purwati, Ayu Endang; Solihah, Rosidah (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Women in the climacteric period will experience certain changes that can cause mild to severe disorders. A woman's readiness or unpreparedness for the menopause can be influenced by the amount or lack of knowledge she has about the menopause. The results of the preliminary study in Sumberjaya Village show that most pre-menopausal women do not understand how to deal with the menopause. In this study, the media used to improve readiness is a climacterium digital pocket book. The aim of this study was to determine the effectiveness of the climacterium digital pocket book on menopause readiness. Method: This study is a pre-experimental study using a one group pretest-posttest design. The population in this study were premenopausal mothers aged 40-50 years totalling 482 people. The sample size was determined using the Slovin formula as many as 83 respondents. The sampling technique was carried out by accidental sampling. This research instrument used a questionnaire and data analysis using the Wilcoxon test. Result: The results of the difference test (Wilcoxon) pretest and posttest data on readiness to face menopause before and after reading the climacterium digital pocket book with a p-value of 0.000 (p <0.05), which means that the climacterium digital pocket book is very effective in increasing readiness to face menopause among premenopausal mothers in Sumberjaya Village. Conclusion: Climacterium digital pocket book effectively improves the readiness of premenopausal women to face menopause in Sumberjaya Village. It is hoped that this climacterium digital pocket book can be used as one of the educational media in other locations, particularly for pre-menopausal.